Potency and species specificity of aryl hydrocarbon receptor ligands - Wall, Richard John (2012)
The aryl hydrocarbon receptor (AhR) binds a wide range of structurally diverse compounds such as halogenated dibenzo-p-dioxins, dibenzofurans and biphenyls which are abundant in the environment. Activation of AhR leads to the regulation of a battery of xenobiotic enzymes including cytochrome P4501A1 (CYP1A1). The purely chlorinated compounds feature in the World Health Organisation’s (WHO) evaluation of dioxin-like compounds derived from a meta-analysis of previous potency data (toxic equivalency factors; TEFs), which is used to calculate the total toxic equivalence (TEQ).